PENERAPAN PERMAINAN PENYEGAR (ICE BREAKING) DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR - Riya Susanah; Dedy Hidayatullah Alarifin (Jurnal Pendidikan Fisika, 2014)
The purpose of this research is for get up motivation learn and get the result of student learned of class X Muhammadiyah 1 Trimurjo high school in study of sains use ice breaking. The subjeck of research of class X Muhammadiyah 1 Trimurjo high school the student are 25 student’s. This research use the plant CAR (Class room Action Research) have 2 siklus, other siklus have 3 face to face and tes too. The tes do it every last siklus, it’s meet the 3rd. The learn student of motivation had observation use angket the content of student and page of chek list the content of observer for observation ice breaking done. To result of research to give diffrent value of good learn motivation and result of study too from I siklus and II siklus the get up. So we can get a point to apply that ice breaking can get up the learn of motivation and result student of study. The result of observation to learn motivation student in siklus I result persentation about 78,25% it’s mean motivation learn of student is high. In siklus II make forward, result persentation the learn motivation of student about 87,5% it’s mean the learn motivation student very high. For result of study also make forward in siklus I persentation like 72%. The siklus II change become 88%. From result observation give a diffrent good value of the learn motivation of result study in siklus I and siklus II to get up. Then i can get ice breaking can forward of learn motivation and result study of student.